Problems of capacity and load-carrying ability use of containers - Котенко, А.М.; Шилаєв П.C.; Шевченко, В.І. (Eastern-European Journal of Enterprise Technologies, 2012)
Actual questions of load-carrying ability use of large-tonnage containers and vehicles were considered. The researches of actual loading of containers on Kharkov – Liski container terminal of Southern railway were studied and statistic characteristics were plotted. The measures on container and vehicle loading augmentation were proposed.